The application of enduring involvement theory in the development of a success model for a craft beer and food festival. Issue 4 (17th August 2020) - Beckman, Eric; Shu, Fang; Pan, Tianyu
Abstract : Purpose: The purpose of this research paper is to examine whether enduring involvement theory plays a role in predicting craft beer and food festival visitors' experience of the festivalscape. Though craft beer and brewing is a growing area of research, there has been limited studies and theory application in this area. Around the world, craft breweries are increasing in number and producing more unique styles of beer as the demand for craft beer increases. Craft beer consumers visit many of these breweries and are attracted to craft beer festivals in which they can sample multiple local, regional, national and international craft beers. Design/methodology/approach: A quantitative methodology was used based on data collected at the site of the festival. Researchers collected 204 useable surveys from visitors attending the North Miami Brewfest in North Miami, Florida, USA. Structural equation modeling was employed to examine the relationships among enduring involvement, festivalscape, satisfaction, revisit intention and word-of-mouth. Findings: The results revealed that enduring involvement is significant in predicting all four factors of festivalscape (food/beverage quality, convenience, facility and festival staff). The festivalscape factors facility, food quality and festival staff predicted festival attendee satisfaction which in turn predicted both revisit intention and word-of-mouth. However, the festivalscape factor convenience did not influence satisfaction. Research limitations/implications: The authors surveyed only one festival in one region in South Florida. Further studies can survey multiple festivals in multiple regions to increase the generalizability of the research model. Enduring involvement theory could be applied to other niche areas in hospitality and tourism in the future (in addition to craft beer tourism). Practical implications: Craft beer festival organizers should appeal to craft beer clubs, breweries and publications to attract those with a commitment to the craft beer industry to their event. People with an enduring, lasting commitment to craft beer are more likely to have a positive experience of the festivalscape at the event. Lastly, festival organizers should focus on the festivalscape factors facility, festival staff and food and beverage quality to influence satisfaction at the event. Originality/value: This project applies enduring involvement theory in a festival setting. The research is further unique by adding enduring involvement as a predictor of festivalscape experience.